Apparent ploidy effects on silencing are post-transcriptional at HML and telomeres in saccharomyces cerevisiae - McLaughlan, Jenny M.; Liti, Gianni; Sharp, Sarah; Maslowska, Agnieszka; Louis, Edward J. (Public Library of Science, 2012)
The repression of genes in regions of heterochromatin is known as transcriptional silencing. It occurs in a wide range of organisms and can have importance in adaptation to the environment, developmental changes and disease. The model organism Saccharomyces cerevisiae has been used for many years to study transcriptional silencing, but until recently no study has been made in relation to ploidy. The aim of this work was to compare transcriptional silencing in haploids and diploids at both telomeres and the hidden mating-type (HM) loci. Transcriptional silencing was assayed, by growth on 5-fluoroorotic acid (5-FOA) media or by flow cytometry, on strains where a telomere or HM locus was marked. RNA levels were measured by quantitative RT-PCR to confirm that effects were transcriptional. 5-FOA assays and flow cytometry were consistent with transcriptional silencing at telomeres and at HML being reduced as ploidy increases which agreed with conclusions in previous publications. However, QRT-PCR revealed that transcriptional silencing was unaffected by ploidy and thus protein levels were increasing independently of RNA levels. At telomere XI left (XI-L), changes in protein level were strongly influenced by mating-type, whereas at HML mating-type had much less influence. The post-transcriptional effects seen in this study, illustrate the often ignored need to measure RNA levels when assaying transcriptional silencing in Saccharomyces cerevisiae.